Efektivitas Penerapan Model Pembelajaran Paikem Dalam Meningkatkan Kognitif Belajar Siswa Pada Mata Pelajaran Alqur’an Hadits - Aisya Umi Khoiro; Dailur Rahman; Sirotol Mustakim; M Asyhari; Hairusik Hairsik (Institut Kariman Wirayudha Sumenep, 2024)
The effectiveness of the PAIKEM learning model in improving students' cognitive learning in the subject of Al-Quran Hadith in class VIII at MTsN. 2 Pamekasan, to determine the effectiveness of the PAIKEM learning model in improving students' cognitive learning. The focus of the research which is the main discussion in this study is: how the application of the PAIKEM learning model in improving students' cognitive learning in the subject of Al-Quran Hadith in class VIII at MTsN. 2 Pamekasan, the effectiveness of the application of the PAIKEM learning model in improving students' cognitive learning in the subject of Al-Quran Hadith in class VIII at MTsN. 2 Pamekasan, as well as supporting factors and inhibiting factors in the application of the PAIKEM learning model in improving students' cognitive learning in the subject of Al-Quran Hadith in class VIII at MTsN. 2 Pamekasan. This type of research uses a qualitative approach based on the results of the research obtained in the form of descriptive data. The data sources of this study are the principal of the madrasah, teachers of the subject of Al-Quran Hadith, and students. The data collection procedures used are observation, interviews, and documentation. While data analysis in this study uses data reduction, data presentation, and data verification. The results of the research conducted by the researcher show that in the learning process using the PAIKEM learning model at MTsN. 2 Pamekasan has been implemented well and the implementation of PAIKEM learning is carried out according to the needs of students. The effectiveness of the implementation of the PAIKEM learning model includes the preparation of learning plans, student-centered activities which means students are more active, carrying out evaluations with various techniques such as: assignments, namely how students work in groups to complete tasks. The implementation of the PAIKEM learning model is well implemented can be seen when the learning process is a conducive classroom atmosphere. Students are more active both when answering questions and expressing opinions. Meanwhile, supporting factors for the implementation of PAIKEM learning are teaching staff, facilities and infrastructure, and student readiness in receiving learning. Factors inhibiting the implementation of the learning model are, lack of time, passive students and lack of enthusiasm.